Defining culturally compelling mental health interventions: A qualitative study of perspectives on adolescent depression in Lagos, Nigeria - Katherine Ottman; Syed Shabab Wahid; Ruth Flynn; Olufisayo Momodu; Helen L. Fisher; Christian Kieling; Valeria Mondelli; Abiodun Adewuya; Brandon A. Kohrt (Elsevier, 2022)
There is growing policy, practice, and research interest in reducing the treatment gap for adolescent depression in low- and middle-income countries, where 90% of the world's adolescents live. Despite increased efforts for adolescent depression services in these settings, there is a risk that services will not be utilized if initiatives are not culturally compelling. Therefore, we propose three considerations for culturally compelling programs and examine how these considerations can be defined using anthropological theories and methods. Consideration 1: public health problems are locally prioritized; Consideration 2: mechanisms of change are locally identified; Consideration 3: programs can be implemented by locally identified actors and institutions. We employed the anthropological concept of ethnotheories of adolescent development to elicit information for culturally compelling interventions using qualitative methods in Lagos, Nigeria, from November 2018 to November 2019. Participants included 13 teachers, 12 social workers, 11 mental health specialists, six health workers, four policy makers, and three parents. Transcripts were analyzed by three researchers using a framework approach (inter-rater reliability ​= ​0.7). For the first consideration, locally defined adolescent mental health problems were aggression, irritability, poor academic performance, substance use, sexual behavior, and social withdrawal/isolation. For the second consideration, perceived mechanisms of change were providing protection from abuse, economic assistance, high-quality schooling, guidance from religious institutions, and emotional support. For the third consideration, key stakeholders were parents, religious leaders, teachers, and peers, with religious institutions and schools as key sites for services. Therefore, rather than be limited to an exclusive focus on interventions for clinical symptoms of depression delivered by mental health specialists in clinical settings, a culturally compelling intervention portfolio for adolescent depression would focus on these locally identified concerns and strategies. This research demonstrates how elucidation of stakeholders' perspectives of symptoms, supports, and structural factors can shape development of culturally compelling mental health initiatives.